Production model in the peruvian aquaculture industry - Quiroz-Flores, Juan Carlos (2022)
This research seeks to validate a production model to improve the production processes of rainbow trout farming in the aquaculture sector of the southern region of Peru. The approach of the production model was determined through the combination of methodologies such as Lean Manufacturing and Business Process Management to facilitate process control, inventory management and production planning. These methodologies were integrated from the review of the literature and the diagnosis made through the collection of primary information from neighboring producers within the department of Junín, in central Peru. The results show the success of the model through its implementation in the fish farms of Junín farmers and a simulation in the ARENA version 14.0 software, in this way optimal results were obtained that show a significant improvement in productivity. The results obtained after the implementation and simulation show an increase of 71.87% in productivity with respect to the initial state, in addition, the production cycle time is reduced by 16.67%. It is concluded that the proposed production model is successful and compatible to improve production processes in the aquaculture sector.